INISIASI BUDIDAYA LELE PADA KOLAM PORTABEL UNTUK PENINGKATAN PENDAPATAN RUMAH TANGGA DI RT. 03 KELURAHAN SUMUR DEWA KOTA BENGKULU - Dwita Oktiarni; Deni Agus Triawan; Oktoviani Oktoviani (Universitas Bengkulu, 2018)
ABSTRACTCommunity service activities are conducted by education and training. The ultimate goal is to use home land for lele cultivation in portable pond for increasing household income. The realization of the purpose is carried out with provision of knowledge and skills in making portable pond using mild steel and tarpaulin. Portable ponds have several advantages such as can be applied to areas with less water, more stable water temperature, and easy harvesting of fish. The results of the dedication activities showed a satisfying response in which participants had high enthusiasm in increasing their knowledge and skills in making portable pond for lele culviation. The success of the activities can also be seen from the innovation of the community through suggestions for making hydroponic based vegetable cultivation systems by utilizing water in portable ponds. Generally, initiation of lele culviation in portable pond can be done in home land. Keywords: portable media, fish cultivation, catfish